Self-esteem Changes of Third Culture Kids When Havruta Discussion Reading Therapy Classes Were Applied - jong-sik ko (Adventist University of Africa, 2024)
Background: Cultural attachments among third culture kids (TCKs) are indefinite because of frequent encounters with different cultural environments. This study was concerned with the changes in the self-esteem of TCKs when havruta discussion reading therapy classes were conducted. Methods: This study used an experimental design. Two international schools in the Philippines were selected, and 26 students aged 13-18 years were randomly assigned to the experimental and control groups. A scale reconstructed by Ga Yeon (1993) was used to measure the respondents' self-esteem. Results: The results indicated that the havruta program positively impacted TCKs' self-esteem, especially at the overall and social levels. Both groups showed no significant differences in overall social, family, and school self-esteem rankings. Conclusion: The findings of this study have implications for education, stakeholders, and future researchers seeking to address the needs of TCKs.